Uso de suplementos em pastagem cultivada de inverno para bezerras de corte - Potter, Luciana (2008)
Aiming to evaluate non apparent relations among individual studies and provide a set of more accurate information about supplement utilization on cool-season cultivated pastures, variables from nine experiments wich tested levels and kinds of supplements offered to beef heifers were analyzed. At first, data were stratified in two groups: with and without supplement utilization. Afterwards, supplements offered in different levels were collected in three groups, to estimate the effect of sources ( by-product , grain , ration ). Pasture was evaluated in relation to the availability, structure, chemical composition and digestibility. For animals and per unit of area, the variables analyzed were average daily gain (ADG), body condition score (BCS), back height, stocking rate and live weight gain per hectare. The addition and substitution rates and the efficiency of transformation of grass and supplement were calculated. The availability and the structure of the grass were similar for both groups. Heifers that received supplement presented greater ADG and ingested grass with lesser neutral detergent fiber detergent. At the end of the pasture utilization, the heifers that received supplement were heavier, higher and presented greater BCS. Females that received ration presented higher average daily gain than heifers that received grain or by-product (P<0,05), while the higher stocking rate were verified when the beef heifers received byproduct (P<0,05), with an increment of 45,1% in relation to the others. The live weight gain per hectare was similar between the different kinds of supplement. The utilization of grains provided better results on individual and per area performance when were given at a rate of 0,8% of live weight (LW). For by-product , grain and ration , the substitution rate were 0,8, 0,1 e 0,0 kg of dry matter (DM) of grass/kg of supplement, respectively. The efficiency of transformation of the supplement into kg of LW was similar (P>0,05) among kinds of supplement. However, when the females received ration, the efficiency of transformation of the grass was higher. The choice of the kind of supplement to use in high quality pastures should be based on the purpose of the production system. Rations provide greater increments on the individual performance while by-products provide greater stocking rate and individual performance.